Cathepsin D mediates tachykinin-induced secondary follicle growth independent of the hypothalamic–pituitary–gonadal axis in mice - Kawada, Tsuyoshi; Aoyama, Masato; Yasuda, Keiko; Satake, Honoo (Frontiers in Endocrinology, 2025)
BackgroundCathepsin D is an aspartic protease responsible for the proteolytic processing of vitellogenin at the early stages of folliculogenesis in oviparous vertebrates. Previously, we identified a multifunctional neuropeptide, tachykinin (TK), as an inducer of cathepsin D that promotes vitellogenic follicle growth in the ascidian Ciona intestinalis type A (Ciona robusta), a sister group of vertebrates. However, no regulatory factor for cathepsin D in the ovary has been identified in vertebrates. Moreover, the involvement of cathepsin D in mammalian folliculogenesis has yet to be investigated.MethodsOvaries of 2-week-old ICR mice were used. Cathepsin D gene expression in the ovaries was examined by real-time PCR. Localization of cathepsin D was shown by immunostaining of ovarian sections. Cathepsin D activity was measured using supernatants from the homogenized ovaries. Mouse follicle growth was evaluated using three-dimensional follicle culture system.ResultsImmunohistochemical analysis revealed that cathepsin D is co-localized with TK receptors in granulosa cells of secondary follicles in the ovaries of two-week-old mice, which are sexually immature and in which the hypothalamus–pituitary–gonadal (HPG) axis is not yet functional. TK treatment of the ovaries significantly increased cathepsin D gene expression and its proteolytic activity. Moreover, inhibition of cathepsin D markedly suppressed the secondary follicle growth.ConclusionCollectively, these results indicate that cathepsin D plays essential roles in mouse secondary follicle growth. Recently, we also demonstrated that ovarian TKs promote secondary follicle growth in mice, primarily in a paracrine/autocrine manner. Combined with these findings, the present study leads us to propose an evolutionary scenario in which TK–cathepsin D signaling functions as a conserved mechanism for HPG axis-independent follicle growth across chordates, which may be more broadly conserved than the vertebrate-specific, HPG axis-dependent systems.